2021
DOI: 10.1017/s0022215121001523
|View full text |Cite
|
Sign up to set email alerts
|

Use of pre-operative calcium and vitamin D supplementation to prevent post-operative hypocalcaemia in patients undergoing thyroidectomy: a systematic review

Abstract: Objective This systematic review aimed to establish the evidence behind the use of pre-operative calcium, vitamin D or both calcium and vitamin D to prevent post-operative hypocalcaemia in patients undergoing thyroidectomy. Method This review included prospective clinical trials on adult human patients that were published in English and which studied the effects of pre-operative supplementation with calcium, vitamin D or both calcium and vitamin D on the rate of post-operative hypocalcae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…Khatiwada and Harris [ 12 ] performed a systematic review on trials using preoperative calcium and vitamin D supplementation in adults. Three of the nine studies included calcitriol treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khatiwada and Harris [ 12 ] performed a systematic review on trials using preoperative calcium and vitamin D supplementation in adults. Three of the nine studies included calcitriol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Protocols were variable and seven out of nine included trials reported significantly reduced rates of postoperative hypocalcaemia (absolute risk reduction for hypocalcaemia 13–59%, absolute risk reduction for symptomatic hypocalcaemia 11–40%). The authors concluded that preoperative treatment should be considered [ 12 ]. These conflicting results are probably due to the use of variable treatment protocols in variable patient populations, making comparison of studies difficult.…”
Section: Discussionmentioning
confidence: 99%
“…As patients with hypocalcaemia may require longer hospitalization, more biochemical studies, extended pharmacological treatments, and additional medical resources, hypocalcaemia has become a burden for the health care system. Thus, some authors have recommended routine supplementation with calcium or vitamin D. A systematic review indicated that 7 out of the 9 trials included reported statistically significantly reduced rates of postoperative laboratory hypocalcaemia (absolute risk reduction, 13–59%) and symptomatic hypocalcaemia (absolute reduction, 11–40%) following preoperative supplementation [ 19 ]. In several guidelines, for patients with a laboratory confirmed vitamin D deficiency (i.e., 25-OHD < 20 ng/ml), an age- and body weight- dependent therapeutic dosage was recommended to be used for 1–3 months; the dosage should be as follows (with ranges dependent on body weight): for neonates 1,000 IU/day; for infants 2,000–3,000 IU/day; for children and adolescents aged 1–18 years 3,000–5,000 IU/day; for adults and the elderly 7,000–10,000 IU/day or 50,000 IU/week [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The major criticism is the lack of a clear PTH threshold for both calcium and vitamin D supplementation. Some authors suggest that PTH may not be the only determinant for the development of hypocalcemia and that other factors may play a major role such as vitamin D deficiency [40], dietary habits [41], and other metabolic disorders such as hypomagnesemia [42,43]. Hypomagnesemia is frequently associated with the use of drugs such as aminoglycosides, cyclosporine, cisplatin, amphotericin B, ACE inhibitors, proton pump inhibitors, and some diuretics (thiazides and loop) [44].…”
Section: Discussionmentioning
confidence: 99%